The rights of a rape victim in Islamic Law - Mohd Noor, Azman; Ibrahim, Ahmad Basri (International Islamic University Malaysia, 2008)
Rape victims undergo double jeopardy as they experience unwanted aggression against their freewill which make them suffer physically and mentally, and at the same time they have to fight to be treated fairly and respectfully within the legal environment. There has been a controversial issue regarding rape prosecution in Islamic legal system as the rape victim would be either charged with zina (illegal sexual intercourse) because of her confession or qadhf (false accusation) as a result of her failure to bring four male eyewitnesses. This paper aims at investigating the fundamental rights of rape victims provided in Islamic law. This will include legal rights to be defended fairly, exemption of punishment, adequate compensation, and other essential rights. This study will explore opinions and arguments of classical Muslim jurisprudents from various schools of law.